2003
DOI: 10.4049/jimmunol.170.4.2037
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Is Sufficient for Respiratory Syncytial Virus G Glycoprotein-Induced Eosinophilia After Respiratory Syncytial Virus Challenge

Abstract: Although well studied in settings of helminth infection and allergen sensitization, the combined contributions of IL-4 and IL-13 and their signaling pathways in models of viral pathogenesis have not been reported. Using a murine model of respiratory syncytial virus (RSV) infection, we evaluated the contribution of IL-13, alone and in conjunction with IL-4, during immunization with recombinant vaccinia virus expressing RSV G glycoprotein (vvGs) or with formalin-inactivated RSV (FI-RSV). We showed that both IL-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 75 publications
(57 reference statements)
7
86
2
Order By: Relevance
“…RSV infection was shown to upregulate the expression of nerve growth factor and its receptors (26), and the presence of G protein was associated with the secretion of substance P, a tachykinin neuropeptide (54). It was also recently demonstrated that IL-13 alone was adequate for G protein-induced eosinophilia (30). Thus, through secretion of cytokines such as IL-13, type 2 T cells in the lungs against G protein could contribute directly to airway hyperresponsiveness, mucus hypersecretion, and inflammation (12,60).…”
Section: Discussionmentioning
confidence: 99%
“…RSV infection was shown to upregulate the expression of nerve growth factor and its receptors (26), and the presence of G protein was associated with the secretion of substance P, a tachykinin neuropeptide (54). It was also recently demonstrated that IL-13 alone was adequate for G protein-induced eosinophilia (30). Thus, through secretion of cytokines such as IL-13, type 2 T cells in the lungs against G protein could contribute directly to airway hyperresponsiveness, mucus hypersecretion, and inflammation (12,60).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to FI-RSV immunized mice, IL-13, but not IL-4, is necessary for the development of pulmonary eosinophilia in vacvG-immunized mice [27,44]. In addition, it has also been shown that treatment of vacvG-immunized mice with recombinant IL-12, a cytokine important in the differentiation of Th1 cells, reduces pulmonary eosinophilia [45,46].…”
Section: The Contribution Of Memory Cd4 T Cells To Rsv Vaccine-enhancmentioning
confidence: 99%
“…The G 183-195 -specific memory CD4 T cell response is comprised of predominately Th1 (IFN-γ and/or tumor necrosis factor-α (TNF-α)-producing) cells with a small proportion of Th2 (IL-4-, IL-5-, and/or IL-13-producing) cells [21,23,27,34,37,[40][41][42]. Interestingly, the diversity of the CD4 T cells capable of recognizing the G protein of RSV appears limited because the majority of RSV G 183-195 -specific memory CD4 T cells express the Vβ14 T cell receptor on their surface [41].…”
Section: The Contribution Of Memory Cd4 T Cells To Rsv Vaccine-enhancmentioning
confidence: 99%
See 2 more Smart Citations